Immunization with lipopolysaccharide-free outer membrane complexes protects against Acinetobacter baumannii infection. Issue 29 (5th July 2018) - Pulido, Marina R.; García-Quintanilla, Meritxell; Pachón, Jerónimo; McConnell, Michael J.
Highlights: OMCs extracted from LPS-free A. baumannii are highly immunogenic. Immunization with OMCs from LPS-free A. baumannii provides protective immunity. The presence of LPS in A. baumannii OMC vaccines contributes to protective immunity. Abstract: Outer membrane complex (OMC) vaccines, which contain antigens from the bacterial outer membrane, have been developed for multiple Gram-negative bacteria. However, OMC vaccines demonstrate high endotoxin activity due to the presence of lipopolysaccharide in the bacterial outer membrane, thus precluding their use in humans. We isolated OMCs from an LPS-deficient strain of A. baumannii (IB010) which completely lacks LPS due to a mutation in the lpxD gene. OMCs from IB010 demonstrated a more than 10, 000-fold reduction in endotoxin activity compared to OMCs from wild type A. baumannii . Vaccination with IB010 OMCs produced similar levels of antigen-specific IgG and IgM after two administrations compared to wild type OMCs, and resulted in a similar reduction in post-infection spleen bacterial loads and serum pro-inflammatory cytokine levels. Vaccination with IB010 OMCs provided significant protection against infection compared to control mice, indicating the LPS-free OMCs could contribute to vaccine strategies for preventing infection by A. baumannii .